(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract This article explores the critical role of feedback in the process of language acquisition. Through various forms of feedback—such as corrective, formative, and peer feedback—language learners receive guidance that aids in skill improvement and comprehension. Drawing on research from books and journals, this article examines how feedback types influence learners' progression in language learning and highlights practical ways educators can implement effective feedback strategies.